Populasi Spodoptera frugiperda di Lahan Jagung pada Pola Tanam Monokultur dan Polikultur - Fahmi Nur Ilham Fajar; Deo Datus Cristy Putra Sirait; Edho Arya Saputra; Muhammad Muis; Reydo Nugraha; Yulia Pujiastuti (Seminar Nasional Lahan Suboptimal, 2021)
Fajar FNI, Sirait DDCP, Saputra EA, Muis M, Nugraha R, Pujiastuti Y. 2021. Population of Spodoptera Frugipeda in the corn field of monocultural and polycultural  plant patterns. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 570-577.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Increased yields on corn cropland are certainly an important factor in meeting the needs of other commodities besides rice. In order to maximize the management can not be arbitrary. It's just that there are some obstacles during its cultivation such as Spodoptera which damage crop yields, so it is necessary to carry out proper and maximum control. The main highlight on Spodoptera pests is S.  frugiperda. Control of Spodoptera frugiperda can be overcome by the use of pesticides but the impact is not too good because it will kill natural predators. The right step can be with the management of polyculture cropping patterns. This is in the form of monoculture and polyculture. The purpose of writing this scientific paper was to determine the population of S. frugiperda in corn fields in monoculture and polyculture cropping patterns. The method used in writing this paper is a literature study method obtained from literature from books and scientific journals on the internet. Based on the results of the literature study obtained, it is known that cropping patterns are related to the life of S.  frugiperda. Polyculture is more effective in preventing this pest from growing well than monoculture. Polyculture cropping patterns can help various kinds of insects increase so that competition between S. frugiperda and natural enemy insects can occur. It was concluded that the population of S. frugiperda differs depending on the crop pattern and it is more effective to use a polycultural cropping pattern interspersed with plants like soybeans to inhibit the population of Spodoptera frugiperda.